"Pig's Nest" in an Even Bigger Pen: Pugad Baboy as a Case of Subversion and Renegotiation in Philippine Comedy - Ancheta, Maria Rhodora G. (Humanities Diliman: A Philippine Journal of Humanities, 2007)
This paper discusses Pol Medina, Jr.'s contemporary comic strip Pugad Baboy as a case of subversion and renegotiation undergone by Philippine comedy. This paper posits that Medina's innovation by way of the "novelization" of the comic strip, as exemplified here by "Ang Hiwaga ng Dueñas" ("The Dueñas Mystery") from Pugad Baboy 4, illustrates and inscribes what can be deemed as comic interpretations of the gaps, distortions, and juxtapositions within Philippine culture. The reading of this contemporary Philippine comic strip leads us to examine abnormality, incongruity, inversions, and hyperreality as manifestations of current Philippine comedy, one that may be socially corrective, or culturally liminal, which now moves towards a depiction of comic postmodernity.